Implications of Implementing Promulgated and Prospective Emission Regulations on Air Quality and Health in India during 2030 - Sreyashi Debnath; Rama Krishna Karumuri; Gaurav Govardhan; Rajmal Jat; Himadri Saini; Akash Vispute; Santosh H. Kulkarni; Chinmay Jena; Rajesh Kumar; D. M. Chate; Sachin D. Ghude (Aerosol and Air Quality Research)
Abstract To improve ambient air quality, India has laid out strict action plans to reduce the increment in emissions over regional to urban scale by the year 2030. This study evaluates policy-induced improvement in air quality and associated health benefits achievable due to reduction in PM2.5 exposure under the adoption of promulgated (S2) and ambitious prospective regulations (S3) with respect to the scenario for Business As Usual (BAU) in 2030. The Weather Research and Forecasting model coupled with online chemistry (WRF-Chem) has been used to simulate ambient PM2.5 exposure to the population under BAU, S2 and S3 emission scenarios. Results show 15% (9 µg m−3) and 49% (32 µg m−3) decreases in all India ambient PM2.5 exposure under S2 and S3 scenarios, respectively, with respect to the BAU scenario. Throughout India, under the S2 and S3 scenarios, 38% and 62% of states would meet the annual National Ambient Air Quality Standard (NAAQS) of 40 µg m−3, respectively. We projected that the S2 emission regulation scenario would prevent 274,000 (8.3%) premature mortalities and improve mean life expectancy by about 0.6 ± 0.2 years in 2030 relative to the BAU scenario. On the other hand, pursuing an ambitious emission scenario, S3 would prevent 775,000 (~23.6%) premature mortality burden and improve mean life expectancy by about 1.9 ± 0.7 years in 2030. Results indicate that ambitious actions beyond the ambitious prospective regulations are vital to gain significant health benefits.